PENGARUH PROMOSI DAN PENGETAHUAN TERHADAP MINAT MASYARAKAT MENGGUNAKAN BANK SYARIAH INDONESIA (BSI) KCP JAMBI SUNGAI BAHAR - Rima Putri Yanti (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the effect of promotion and knowledge on public interest in using Indonesian Islamic Bank (BSi) KCP Jambi Sungai Bahar. There are many strategies that can be done to attract people's interest to use Bank Sayariah, one of them is by promotion. In this day and age, promotion can be done in many ways, namely, using social media, advertising, and so on. In addition, banks must also provide knowledge to the public about the products/services offered by Islamic banks so that they can increase public interest in using Islamic banks. This type of research is quantitative research. The population in this study is the community around Tanjung Sari Village. The sampling technique used the slovin technique with a sample determination of 100 people. Data collection techniques in this study through observation, interviews, distribution of questionnaires, and documentation. Furthermore, data processing and analysis techniques use the help of the SPSS program. The stages in data processing and data analysis techniques are testing the quality of research instruments, namely validity and reliability tests . Furthermore, the classical assumption test will be carried out consisting of normality test, multicollinearity test, heteroscedasticity test . Then, this study will use multiple linear regression analysis techniques. Partial test results on the promotion variable t arithmetic value > t table ( 4.719 > 1.985 ) and a significance value of 0.000 < 0.005 thus H 0 is rejected and H 1 is accepted. Furthermore, the knowledge variable t arithmetic value > t table ( 4.645 > 1.985 ) and a significance value of 0.000 < 0.005 , thus H 0 is rejected and H 1 is accepted. So, the promotion and knowledge variables affect people's interest. While the results of simultaneous testing with the values of the F test results for promotion (X 1 ) and knowledge (X 2 ) simultaneously on public interest (Y) is 0.000 < 0.005 and the calculated F value > F table ( 47 , 160 > 3.09). So it can be concluded that Ha is accepted and H 0 is rejected, which means that there is a significant influence between the promotion variable and the knowledge variable simultaneously on the public interest variable . The implication of this research is that it can increase knowledge and sources of information about the effect of promotion and knowledge on public interest.